Kationické antimikrobiální peptidy - Neubauerová, Tereza; Macková, Martina; Macek, Tomáš; Koutek, Bohumír (Chemické listy, 2009)
The resistance of microorganisms to antibiotics is an increasing public health problem. Hence, Hence, substances with new mechanisms of antimicrobial action, such as cationic peptides, are of interest. Cationic peptides play an important role in the innate immunity of all living organisms. Over 700 of the peptides have been isolated. Half of them were isolated from insects; their biosynthesis was described. They show a broad antimicrobial activity and act against tumor cells and viruses.
Keywords: kationické antimikrobiální peptidy; Antimicrobial Cationic Peptides; buněčná imunita; polymyxiny; Defensins; Polymyxins; financování organizované; Anti-Bacterial Agents; Financing, Organized; Immunity, Cellular; antibakteriální látky; defensiny